Natural Resources, Openness and Income Inequality in Iran - Sayed Mahdi Mostafavi; Mehdi Behname; Hamideh Mohtashami Borzadaran (Romanian Economic Journal, 2013)
The aim of this paper is to survey the relationship among natural resource, income inequality and openness in Iran by using the Auto Regressive Distributed Lag (ARDL) model in the period 1980-2009. The stationary test reveals that our variables are both I(0) and I(1), so for that reason, we used the ARDL approach to estimate long run and the short run relations between the variables. The results show that, in the long-run and the short-run, the GDP per capita, Land, Openness and literacy rate have a negative effect on income equality; the total natural resource rents has a positive effect on income equality. The oil revenue has a negative effect on income inequality in the short run, and it has a positive effect on income equality in the long run.